The Impact of International Outsourcing on Labour Market Dynamics in Germany - Ronald Bachmann; Sebastian Braun (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2008)
Using an administrative data set containing daily information on individual workers' employment histories, we investigate how workers' labour market transitions are affected by international outsourcing. In order to do so, we estimate hazard rate models for match separations, as well as for worker flows from employment to another job, to unemployment, and to nonparticipation. Outsourcing is found to have no significant impact on overall job stability in the manufacturing sector, but it is associated with increased job stability in the service sector. Furthermore, the effect of outsourcing varies strongly across skill levels and age groups. This is especially the case in the manufacturing sector, where the hazard of transiting to nonemployment rises with international outsourcing for medium-skilled and older workers.
Keywords: F16; J63; J23; 330; Job stability; labour market transitions; worker flows; outsourcing; duration analysis; Arbeitsmarkt; Arbeitsmobilität; Matching; Offshoring; Industrielle Beschäftigung; Outsourcing; Arbeitsplatzsicherung; Deutschland